Pathological Feature and Immunoprofile of Cystitis Glandularis Accompanied with Upper Urinary Tract Obstruction. (29th May 2014) - Li, Aihua; Zhou, Jun; Lu, Honghai; Zuo, Xiaoming; Liu, Sikuan; Zhang, Feng; Li, Weiwu; Fang, Wei; Zhang, Binghui
Abstract : Objective . To explore the pathological feature and immunoprofile of immunoprofile accompanied with upper urinary tract obstruction and the immunoprofile in various types of glandular cystitis. Methods . Pathological sections from 31 cases of cystitis glandularis with upper urinary tract obstruction and 34 cases of cystitis glandularis without upper urinary tract obstruction were observed as pathological feature on microscopy. Meanwhile, an immunohistochemical analysis was employed to determine the expression of p53, Ki67, p21, MMP-9, MUC1, MUC2, and COX-2. Results . In the two groups, main pathological type was transitional epithelial, followed by intestinal epithelial; other types were a few, and the difference between the two groups was not significant. All immunohistochemical expressions of p53, Ki67, p21, MMP-9, MUC1, MUC2, and COX-2 were positive in varying degrees, and there was no significant difference between the groups. Transitional epithelial type was compared with mixed type; the difference of COX-2 was significant, P < 0.05 . The differences of immunohistochemical expression among other different pathologic types were not significant. Conclusions . It is suggested that glandular cystitis accompanied with upper urinary tract obstruction shares the same pathological feature and immunoprofile as that without upper urinary tract obstruction. No significant differences of immunohistochemical expression in tissue are in cystitis glandularis with different pathological types.